IUTAM Symposium on Synthesis in Bio Solid Mechanics Proceedings of the IUTAM Symposium held in Copenhegen, Denmark, 24Ớ<U+001c>27 May 1998 - Pedersen, Pauli.; Bends©ıe, Martin P. (Solid Mechanics and its Applications,, 2002)
This book contains the edited version of invited lectures presented at the IUTAM-Sym- sium Synthesis in Bio Solid Mechanics, held at Hotel Frederiksdal, Virum (Copenhagen), Denmark, May 24 to May 27, 1998. The symposium was attended by 48 scientist from 14 countries. Biomechanics has been a very active research area in the last 25 years and covers a very broad class of problems. The present symposium concentrated on the solid mechanics - main of biomechanics, where important problems of synthesis presently are an active and challenging part. Characteristics of biomechanical materials are not only the inhomogeneity and anisotropy, but also the capability to change in relation to actual use. These living materials call for new methods of analysis and also new methods for synthesis. By the synthesis in this context is meant design of implants or artificial control of material growth. Bone mechanics is closely related to recent work on analysis and design of microstructural anisotropic materials. Also, recent work in shape design can to some extent be useful in the more complicated problems of biomechanics. Here interface problems play an essential role. The symposium brought together scientists from mechanics, mathematics and medicine.